Fatigue Failure Analysis of a Gear in Automobile Engine Coolant Pump. (27th March 2022) - Krishnasamy, Krishnakumar; Subbulekshmi, D.; Deepa, T.; Gnanasekaran, B. M; Maridurai, T.; Sriram, M.; Kumar, Srinivasan Suresh; Markos, Mebratu
Abstract : Gear is a reliable part of power transmission. This article presents a metallurgical failure analysis of a failed gear used in automobile engine coolant pumps. In gear, the soft microstructure of pearlite and ferrite is witnessed in metallographic analysis. Significant wear is perceived in gear teeth, and significant deformation is observed in the keyway. The crack initiated from the corner radius of the keyway and propagated towards to the root of the teeth, which is evidence of the failure due to fatigue. Recommendations are given to improve the fatigue strength of gear.